Bimetallic ZnCo nanorod array for highly reactive and durable hydrogen evolution reaction. (5th January 2022) - Zhu, Jianmin; Xu, Lishuang; Zhang, Shuai; Yang, Ying; Huang, Licheng; Zhang, Xiao; Wang, Tingting; Wang, Xinlu; Dong, Xiangting
Abstract : One-step hydrothermal method to synthesize a stable ZnCo2 (OH)F nanorod array structure supported by nickel foam. Abstract : The search for efficient non-precious metal or earth-abundant electrocatalysts is the key to drive clean energy technologies to develop a hydrogen economy. Here, we have developed a simple and scalable strategy for the synthesis of bimetallic ZnCo2 (OH)F rod-like nanoarrays supported on nickel foam. The electrochemical test results show that ZnCo2 (OH)F/NF exhibited a good electrocatalytic performance in the hydrogen evolution reaction (HER) at 10 mA cm −2, with an overpotential of 121 mV, a significant Tafel slope value of 129.9 mV dec −1 and excellent stability at different current densities. Due to bimetallic hybridization, this material has excellent catalytic activity and good H* absorption free energy active sites, which indicate its operability in rational hydrogen production applications. This work provides a superior synthetic strategy for the effective design and rational fabrication of low-cost, highly active, and highly stable non-precious metal HER electrocatalysts for electricity-to-hydrogen applications.